TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK) DALAM PENDIDIKAN ISLAM - Muhammad Fauzi; Moh. Samsul Arifin (AL - IBRAH, 2023)
The goal of the study is to examine further the use of information and communication technology in the realm of Islamic education, especially in the field of education. Islamic education has become the main focus in many Islamic countries around the world. In this digital era, Information and Communication Technology (ICT) plays a crucial role in the development of Islamic education. ICT has brought many changes to the Islamic education system, ranging from learning methods to administrative management. This article discusses the use of ICTs in Islamic education, its benefits, and how its use can maintain Islamic values. First, the use of ICTs in Islamic education has allowed distance learning. In distance learning, teachers and students can communicate using video conference technology. This method is very helpful for those who live far from the education center or do not have the financial ability to study in a distant place. The use of ICTs also allows students to have access to educational resources such as books, articles, and videos online. A wise decision was made to use ICT in Islamic education through the development of Islamic education applications. This Islamic education application can be used to facilitate students in accessing subject materials or extracurricular activities. Some Islamic education applications also offer interactive features that can help students understand the subject matter in a more meaningful way. Third, the use of social media can also help expand the reach of Islamic education. Many Islamic education communities have used social media as a platform to share information and promote education activities. However, it should be remembered that the use of ICTs in Islamic education could also pose risks. Inaccurate information, negative content, and misuse of technology are some of these risks. Therefore, it is critical to maintain Islamic values in the use of ICT in education. This can be done by developing ICT platforms that are in accordance with Islamic principles. In addition, it can be done by educating students about the use of ICTs that are responsible and in accordance with Islamic values. The use of ICTs also needs to be carefully monitored to ensure that Islamic values are maintained. Therefore, the use of ICTs in Islamic education needs to be developed. In this study, the library method, or what is known as library research, analyses literature, books, notes, and various other reports related to the problem. integration of this technology has many benefits that can be put into practice.